Making Hate Visible: Online Hate Incident Reporting Tools - Irfan Chaudhry (Journal of Hate Studies, 2021)
Given the recent number of hate-related incidents that have come to public attention, there is a significant need to collect and track these incidents in order to capture and share trends with the wider public. Outside of official hate crime data (such as annual government reports), incidents fueled by hate (but that are not crimes) often go undocumented. To address this gap, the Alberta Hate Crimes Committee – a Canadian coalition of law enforcement, government, and non-governmental organizations – developed the StopHateAB.ca website. The purpose of the StopHateAb.ca website is to fill this gap by creating a space to capture hate incidents to document and make accessible information related to hate incidents. This article will describe the development of the online hate incident reporting tool StopHateAB.ca. Through a discussion of the strengths and challenges of creating an online hate incident reporting platform, this paper will highlight the importance of innovative responses to counter hate and bias by making hate visible. As this article highlights, making hate visible forces communities to engage in joint conversations about hate and bias to support strategies that foster a public social environment of justice, equity, and human rights.